Implementation of a Non-Invasive Bioprospecting Protocol for Isolation of Lactobacillus from Feces of Hens Under Foraging Conditions (2018)
In animal production, probiotics seek to replace the use of antibiotics, while diminishing mortality and morbidity rates to raise productivity. Probiotics constitute a natural alternative that, in contrast with antibiotics, neither produces pathogen resistance, nor leaves chemical residues in the final product. Several bacteria, including some belonging to the genus Lactobacillus have been described as probiotics with high potential. A non-invasive bioprospecting protocol aimed for the isolation and characterization of lactobacilli from chicken feces was established. Fecal samples were collected from the ground. These were diluted and cultured in LAB selective medium. Colonies were identified by three methods: Gram stain, MALDI-TOF MS and sequencing of 16S rRNA gene. An initial probiotic potential of lactobacilli isolates was determined via antagonism tests using five enteropathogen reference strains: Staphylococcus aureus, Enterococcus faecium, Candida albicans, Pseudomonas spp. and Salmonella spp. 24 isolates belonging to four Lactobacillus species were identified by MALDITOF MS. BLAST of 16S rRNA gene of eight randomly selected isolates, confirmed MALDI-TOF MS identification. Five of these eight isolates inhibited the growth of at least one of the pathogenic strains used, three isolates of Lactobacillus plantarum and two of Lactobacillus salivarius. Our protocol achieved 21 lactobacilli per 100 isolates performance, greatly surpassing the normal percentage of lactobacilli in chicken gut microbiome, that so, its implementation would facilitate the isolation and identification of new probiotic strains from feces.